Adhesion promoter for a multi-dielectric-layer on a digital microfluidic chip1. Issue 60 (2nd July 2015) - Gao, Jie; Chen, Tianlan; Dong, Cheng; Jia, Yanwei; Mak, Pui-In; Vai, Mang-I.; Martins, Rui P.
<x xml:space="preserve">Abstract</x> A silane-based adhesion promoter suitable for a multi-dielectric-layer coating on a digital microfluidic chip is reported.